A report on the practice-in-industry training in fish preservation. - Batangantang, Victoria (1954.)
Contained in this report is a summation of the six months practice in industry training in fish preservation course. The work concerns the actual application of the knowledge earned during the course of studies primarily to gain a thorough understanding of preservation from simple to a more complex one. In all lines of preservation however, there is but one underlying principle to which all the objectives fall, and that is the creation of unfavourable condition to retard agent of spoilages, growth and disable them to survive thus assuring as a result of a better keeping quality product. Nature plays an important role too in making the product last long, and as such proper handling of the finished product should be applied.
Report (Undergraduate. Fish Preservation) College of Fisheries, University of the Philippines, 1954.
Keywords: Fish preservation